Vertebral Tongue-Like Deformity in Mucopolysaccharidosis VI. Issue 1 (27th September 2021) - Landen, Michiel; Eyskens, François; Vanhoenacker, Filip
Teaching point: Defective development of the anterior portion of the vertebral body at the thoracolumbar junction may be an important imaging clue in the diagnosis of mucopolysaccharidosis.